Merawat Mistisisme dalam Tradisi Ngalap Berkah di Era Modern sebagai Upaya Menjaga Tatanan Sosial Bermasyarakat di Pasar Kliwon Solo - Habibi, M. Said (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2023)
Mysticism which is known as commonplace in society is an interesting phenomenon to be studied, This article discusses caring for mysticism in the tradition of ngalap berkah in the modern era as an effort to maintain social order in Pasar Kliwon Solo, the tradition of mysticism is a habit in society, in this study uses analytical descriptive research methods to explain how the tradition of ngalap berkah in the context of mysticism. This study concludes that caring for mysticism in the tradition of ngalap berkah is one of the effective solutions in establishing friendship in society, besides that it also indicates how urgent a person is in maintaining social order in modern times.